# Yahoo Web Search

1. ### Can you help me with the trigonometric function of a ferris wheel?

Y=Asin( B ( T -H))+ K This is a function ... the graph of Y=Asin( B ( T -H))+ K upwards. H is the horizontal...

1 Answers · Science & Mathematics · 10/05/2014

2. ### Which of the following is NOT a valid cell reference?

=\$ B \$ K

1 Answers · Computers & Internet · 20/04/2012

3. ### Learning Korean (can' t hear difference between b /p, t /d, k /g)?

... syllable ㅋ Is a strong K ㄷ as a light but d if it is... syllable ㅌ is a strong T ㅂ is a light p but b if it is not the first syllable...

2 Answers · Travel · 24/09/2009

4. ### Anyone seen the B . T . K . movie?

I've seen it and you were wise to pass it up. I'm a huge true-crime buff and I can tell you that as fiction, this story would suck. The fact that they claim it's based on real events should make it illegal. It bears no resemblance to the real story...

2 Answers · Entertainment & Music · 25/07/2009

5. ### Solve each equation for indicated variable?

B + K /J = T K /J = T - B K = J*( T - B ) - b /c + 5 = d - b + 5c = cd - b = c*(d - 5) c = - b / (d - 5)

3 Answers · Science & Mathematics · 17/08/2012

6. ### W.O. B .A. T on J. K Rowling s website?

... with an O for Outstanding, T for Troll etc. You can access ... on the eraser on the home page (J. K . Rowling's desk). This will take...

2 Answers · Arts & Humanities · 30/10/2008

7. ### Which two WRs would you start?

B .Quick for sure. He's been consistent. I like K .Benjamin more; but I am not sure about the other two.

1 Answers · Sports · 11/10/2014

y = A sin [ B ( t - h)] + k and y = A cos [ B ( t - h)] + k ...39; t mess up the signs: y = 7 sin [4( t - -7)] + -8 ... so A = 7, B = 4, h = -7 and k = -8 Then you can just write out whatever...

2 Answers · Education & Reference · 03/05/2012

9. ### Prove log( b ^ t )= t * log b ?

Let b =10^ k then k = log b Then b ^ t = 10^(kt) It follows that log( b ^ t ) = log( 10^(kt) ) = kt = t * log b .

1 Answers · Science & Mathematics · 30/03/2011

10. ### Show that the function has a maximum at E = (( b * k * T )/2)^2/3?

Given: f(E)=e^(-(E/( k ∗ T ))−( b /√E)) = {e^(-(E/( k ∗ T )))}{e...)))}{e^−( b /√E)} + {e^(-(E/( k ∗ T )))}{- b (-1/2)(E^(-3/2))e^−( b /√E)} ...

1 Answers · Science & Mathematics · 12/02/2013